The effect of swiftlet nest cleaning process on the nitrite and protein contents - Mohd Taib, Siti Husnaa; Abd Gani, Siti Salwa; Ab. Rahman, Mohamad Zaki; Basri, Mahiran; Shamsudin, Rosnah (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Swiftlet nest (SN) is a nest that is produced by different species of swiflets in the genus Aerodramus and Collocalia during the breeding season. It is widely consumed as a health food product for its high beneficial effects to human being. In recent years, the swiftlet nest industry is facing a difficult time because of the high level of nitrite detected in edible SN. This study was conducted to determine the nitrite and protein content of raw and processed SN. The study showed that raw SN has low concentration of nitrite whereas processed SN was devoid of nitrite. Analytical results showed that raw and processed SN exhibited high protein content (56.9%-60.9%) which did not differ significantly before and after processing of SN. In conclusion, cleaning process could reduce the nitrite content and preserve the protein content in SN. API Nitrite test kit is a useful tool and rapid method for the determination of nitrite content in swiftlet nest.